MENDESKRIPSIKAN KETERAMPILAN PROSES SAINS MAHASISWA PENDIDIKAN FISIKA UNIVERSITAS JAMBI PADA METARI PEMBIASAN PADA LENSA CEMBUNG DENGAN MENGGUNAKAN E- MODUL - Aziza Putri Ningsi; Neng Ria Nasih (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
When the process of teaching physics is done conventionally, students tend to only master the concepts of physics without knowing the process of the occurrence of these concepts. Science process skills are the ability to process actions as well as scientific thought in order to develop an understanding of scientific concepts to support subsequent abilities. practicum is a supporter of the quality of education that improves student process skills, namely science process skills, with the e-module can facilitate the practicum process. This research was conducted aiming to find out the science process skills of physics education students for refracting material on the convex lens. From the results of the study. it can be seen that the results of the process skills of students' skills can be said to be good, because most students are already skilled in practicing. With the use of the Guidebook for Basic Physics II practicum in the form of e-modu can increase students' science process skills.